FINANCIAL PERFORMANCE ANALYSIS BEFORE AND AFTER THE INITIAL PUBLIC OFFERING (IPO) AT PT DAYA CIPTA INTEGRASI INDONESIA TBK (DCII) FOR THE PERIOD 2020-2024 - Eva Khadijah; Amar Khadafi (International Journal Management and Economic, 2026)
An Initial Public Offering (IPO) is a company's strategy to obtain additional capital and increase transparency of financial performance. This study aims to analyze the financial performance of PT Daya Cipta Integrasi Indonesia Tbk (DCII) before and after the IPO based on liquidity, solvency, and profitability aspects using financial report data for the 2020–2024 period obtained from the Indonesia Stock Exchange (IDX) and the company's official website. The research method used is documentation and literature study. The data analysis technique used is quantitative descriptive analysis by calculating liquidity ratios consisting of the Current Ratio, Quick Ratio, and Cash Ratio, solvency ratios consisting of the Debt to Asset Ratio and Debt to Equity Ratio, and profitability ratios consisting of Net Profit Margin, Return on Assets, and Return on Equity. The results of the study indicate that after the implementation of the Initial Public Offering (IPO), the financial performance of PT Daya Cipta Integrasi Indonesia Tbk has changed. The company's liquidity performance is still below industry standards, solvency performance is in good condition with a low level of dependence on debt, while profitability performance shows good results and is above industry standards.